Development and validation of children's mind wandering scales - Cao, Zhiwei; Huang, Ying; Song, Xiaolan; Ye, Qun (Frontiers in Public Health, 2022)
Mind wandering is one of the most common mental states and typically occurs at a significant cost to mental health and behavioral performance. The measurement of mind wandering is essential for learning its effects and causes. Several measurements have been developed in the past few decades to assess mind wandering in adults, but there are no scales especially for children. The present studies aimed to develop the Frequency of Children’s Mind Wandering Scale (CMWS-F) and the Context of Children’s Mind Wandering Scale (CMWS-C) to assess the frequency of mind wandering and the contexts in which mind wandering occurs for children aged 8 to 11 years. In study 1a, the exploratory factor analysis (n = 292) and confirmatory factor analysis (n = 346) supported attentional failure and spontaneous thinking were two main dimensions for CMWS-F; in study 1b, the contexts of mind wandering in children could be divided into high-demand and low-demand contexts by using exploratory factor analysis (n = 258) and confirmatory factor analysis (n = 347). In study 2, scores on CMWS-F and CMWS-C were compared with probe-caught mind wandering in four laboratory-based tasks. The results showed that the scores on the two scales could predict the performance on the experimental tasks and further demonstrated the empirical validity of the CMWS-F and CMWS-C scales. Taken together, the results of the current studies provided preliminary evidence for the validity and reliability of CMWS-F and CMWS-C in children, which can be used as a reference to balance its downsides and productive aspects of mind wandering.